Prevalence and Predictors of Post-Traumatic Stress Disorder and Depression Among Survivors Over 12 Years After the Bam Earthquake - Divsalar P (Dove Medical Press, 2020)
Parisa Divsalar,1 Tania Dehesh2 1Neuroscience Research Center, Institute of Neuropharmacology, Department of Psychiatry, School of Medicine, Kerman University of Medical Sciences, Kerman, Iran; 2Department of Biostatistics and Epidemiology, Kerman University of Medical Sciences, Kerman, IranCorrespondence: Tania Dehesh Email Tania_dehesh@yahoo.comPurpose: The Bam earthquake was one of Iran’s worst natural disasters. As a reason of limited sample size, prevalence and risk factors of PTSD and depression were still unclear after a huge earthquake in Bam.Patients and Methods: A total of 1500 participants selected from the survivors by multistage sampling. Instruments included the demographic questionnaire, the PTSD Checklist-Civilian Version and the Beck Depression Inventory-2. Bivariable and multivariable logistic regressions were used to analyze the data.Results: The prevalence rates of PTSD and depressive symptoms were 38.7% (n = 581) and 40.1% (n=597), respectively. The most commonly occurring symptoms of PTSD were distress at reminders (73.7%), fear of recurrence (70.3%) and sleep disturbance (68.4%). Age (OR=1.5, 95% CI= [1.03, 1.74], P < 0.001) and being injured (OR=1.68, 95% CI= [1.09, 2.61], P=0.02) are positive risk factors of PTSD. The risk factors for depressive symptoms were old age (OR= 1.46, 95% CI= [1.02, 1.64], P < 0.001), female gender (OR=1.42, 95% CI=[1.14, 1.77], P=0.002), and death of work colleagues (OR=4.03, 95% CI= [1.54, 6.54], P=0.005).Conclusion: Professional and effective mental health services should design programs in order to aid the psychological wellbeing of the population focusing on older adults, females, those who lost work colleagues, and those who lost their family members.Keywords: Bam, earthquake, epidemiology, depression, PTSD, risk factors